Portrayals of the Arab spring in the electronic media news and the image of Arabs among Malaysian academicians / Somia Abdul-Same’e Anam - Abdul-Same’e Anam, Somia (Institute of Graduate Studies, UiTM, 2017)
This study is a media effects research and it is an attempt to examine the type of Arab image, level of Arab Spring awareness among Malaysian academicians, attitude toward Arabs, perception on new status of the Arabs and the news sources that Malaysian academicians depended on to gain news and information about the Arab World. Specifically, the research objectives are to validate and proposes measurement models, validate and propose a full structural model of news exposure influence in the construction of the image of Arab and estimates the influence of attitude and awareness of Arab Spring as mediator factors, as well as to examine the moderation effect of the variables. This study employs correlational survey as the methodology of study. A total of 300 Malaysian academicians from five public universities located in Klang valley were selected as the sample. For data analysis, the study employs Structural Equation Modelling (SEM) method using AMOS statistical software to analyze the direct and indirect influence of moderator and mediator variables in the relationship between variables and employs SPSS software to analyze the descriptive part of the data. The findings suggested that the internet was a main news source used by Malaysian academicians and Arabs have a moderate image among Malaysians…